Avaliação dos fundos setoriais sob a ótica da hélice tripla - Pontes, Roberto José Almeida de (2008)
This paper deals with the evaluation of Sectional Funds (FSS) and its impacts, as a tool for financing the research and scientific development of the current National Innovation System. The analysis follows the principles of the model of Triple Helix (HT), that it is the arrangement that allows a methodological understanding of how government, the scientific and technological fields as well as the productive sector have the institutional basis for the incorporation of funds the National System of Innovation. The assessments of the achievements started by its distribution sector and implementing the various initiatives in support of infrastructure, knowledge generation of S & T, scientific production, encouragement of R & D in academia and industry, generation of patents on innovative products and innovative processes, beyond the perception as a tool to shield the officials responsible for the creation of an atmosphere of consensus for the country's competitiveness and reducing regional inequalities. The research was conducted on the basis of data provided by official bodies and reviewing the writings of the principal authors as a way to substantiate the tests in question. The issue of contingencies and its repercussions on the FSS have been addressed so analytical in order to offer a critical view on them. Given its innovative aspect, the management of funds was seen checking up its performance in implementing the managed resources. The findings on the impacts of the FSS are offered at the end in order to contribute to the topic.